Greener extraction‐chemical modification‐polymerization pipeline of vernolic acid from Ethiopian ironweed plant. Issue 24 (25th March 2022) - d'Almeida Gameiro, Mariana; Jacob, Philippa L.; Kortsen, Kristoffer; Ward, Thomas; Taresco, Vincenzo; Stockman, Robert A.; Chebude, Yonas; Howdle, Steven M.
Abstract: Epoxidized oils are commonly used in the plastics industry as additives in the formulation of polyvinyl chloride (PVC) and as monomers in the coating industry. They are produced from petrochemical feedstocks or by chemical epoxidation of natural oils. Currently, the synthesis processes of these materials are expensive, utilize volatile organic solvents and hazardous oxidants, which are unfavorable for the environment. There is a need to find natural epoxidized oils. Vernonia galamensis ( ironweed) is a plant found in abundance in Ethiopia with no commercial value, but its seeds contain 40 wt% epoxide rich triglycerides. V. galamensis oil contains up to 80 wt% of vernolic acid (VA), a mono‐unsaturated fatty acid with an additional epoxide functionality. The presence of alkene and epoxide(oxirane) groups offers excellent opportunities to synthesize new building blocks for polymerisations. Here, we report a green and efficient extraction methodology (up to 80% of extraction‐efficiency) of the triglyceride vernonia oil from V. galamensis using supercritical carbon dioxide (scCO2 ). We then report the synthesis of a series of polymerisable monomers (conversion in monomers 64%–99%) based on the VA obtained from the saponification process. Finally, the novel monomers are polymerized into different polymers through polycondensation using a mixture of metal‐based and enzyme catalysts. Abstract :